IMPLEMENTASI MONITORING PEMBIAYAAN MUROBAHAH DI BMT MASLAHAH CABANG JEMBER TAHUN 2023 - Supriyanto; Adi Suwarno, Suparjo (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
The purpose of this study is to describe the implementation of Murobahah Financing monitoring at BMT Maslahah Jember Branch in 2023 where there are many benefits of monitoring among the effectiveness of returning loans from creditors in Islamic financing, especially at BMT Maslahah Jember Branch in 2023. Monitoring also serves to assess the extent to which the implementation of murabaha has a positive impact on Islamic financing.